A model of choice from lists - Ariel Rubinstein; Yuval Salant (Theoretical Economics, 2006)
The standard economic choice model assumes that the decision maker chooses from sets of alternatives. In contrast, we analyze a choice model in which the decision maker encounters the alternatives in the form of a list. We present two axioms similar in nature to the classical axioms of choice from sets. We show that they characterize all the choice functions from lists that involve the choice of either the first or the last optimal alternative in the list according to some preference relation. We then relate choice functions from lists to the classical notions of choice correspondences and random choice functions.
Keywords: D00; 330; Choice from lists; rational choice; partition independence; weak axiom of revealed preference; satisficing